2015
DOI: 10.1007/s12275-015-4686-3
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial potential of a small peptide from Bacillus sp. RPT-0001 and its capping for green synthesis of silver nanoparticles

Abstract: Infirmity and death from diseases caused by unsafe food are a continual hazard to communal health safety and socio-economic growth throughout the world. Chemical preservatives are associated with health hazards and toxicity issues. In the study reported here, 200 soil isolates from Western Himalayan region in India were screened for potential antibacterial activity against food-borne pathogens. This study led to the isolation of a bacterial strain belonging to the Genus Bacillus and was designated as RPT-0001.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Bacteriocin is a small heat-stable peptide which has a bactericidal effect on pathogenic microorganisms [112]. The bacteriocin derived from the microbes could act as a reducing agent for the synthesis of metal NPs [113]. In addition, previous study has proved that this small peptide could also bind to the surface of NPs as a capping agent which in turn enhance the antimicrobial effects of metal NPs [112–116].…”
Section: Introductionmentioning
confidence: 99%
“…Bacteriocin is a small heat-stable peptide which has a bactericidal effect on pathogenic microorganisms [112]. The bacteriocin derived from the microbes could act as a reducing agent for the synthesis of metal NPs [113]. In addition, previous study has proved that this small peptide could also bind to the surface of NPs as a capping agent which in turn enhance the antimicrobial effects of metal NPs [112–116].…”
Section: Introductionmentioning
confidence: 99%
“…These biosynthesis results are in consonance with similar studies conducted by different researchers. The absorption peak at 420 nm was reported by Patil et al [11] using Bacillus species RPT0001 in conjugation with SNPs. Singh et al [24] reported absorption peak at 450 nm using partially purified bacteriocins extracted from lactic acid bacteria.…”
Section: Resultsmentioning
confidence: 68%
“…The production and partial purification of bacteriocin were carried out according to the method described by Patil et al [11], and Sharma et al [17] with slight modifications. An overnight grown culture of L. brevis MTCC 4463 (standard strain) and the isolate L. herbarum was centrifuged at 10,000 rpm for 15 min at 4°C and the cell-free supernatant was collected.…”
Section: Production and Partial Purification Of Bacteriocinsmentioning
confidence: 99%
See 1 more Smart Citation
“…BiomassSpherical50 and 100 M. smegmatis M. smegmatis and M. marinum [182]Bacitracin A and polymyxin EAgNPsSpherical3.1 E. coli , B. amyloliquefaciens , P. aeruginosa and S. aureus Promotes healing of infected wounds[181]G 3 R 6 TATAgNPs-citrateAgNPs-SDS and Au@Ag-BSATriangularSpherical30–7030 B. subtilis , E. coli and C. albicans [165]LL-37CYS-modified (LL37-SH)AgNPsSpherical5.3 ± 1.8No anti-proliferative effect on primary skin cells; promotes wound healing, preventing potential infection by E. coli , Staphylococcus epidermidis , S. aureus , and free living and biofilm forms of P. aeruginosa [210]NisinAgNPs incorporated in poly( d , l -lactide) (PDLLA) and poly(ethylene oxide) (PEO) nanofibers-21.81 ± 5.5 P. aeruginosa , Klebsiella pneumoniae , E. coli , S. typhimurium and S. aureus [211]RPT-0001AgNPsSpherical20–30Against food-borne bacterial pathogens: L. monocytogenes , Cronobacter sakazakii , S. enterica subsp. enterica and E. coli [212]IndolicidinCOOH-functionalized AuNPsSpherical3Immuno suppressive action by downregulation of IFNβ expression and increase of IL-10 in RAW264.7 murine macrophage cells and THP-1 human monocyte cell lines…”
Section: Table A1mentioning
confidence: 99%